Assessing Household Financial Behavior During COVID-19: A Focus on Expenditure and Savings - Efriyani Sumastuti (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to investigate the effects of the COVID-19 pandemic on household expenditure, savings, and financial behavior in low- to middle-income households in Indonesia. The research analyzes how the pandemic influenced household financial management, particularly in terms of spending reductions and shifts in saving behaviors. Data were collected from 100 households through structured surveys, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The methodology allowed for both direct and indirect relationships between household expenditure, savings, and the economic shock of COVID-19 to be explored. The results indicate a positive correlation between household expenditure and savings, where higher-income households were able to save more despite greater spending. However, the pandemic negatively impacted both expenditure and savings, with households reducing non-essential spending and relying on their savings due to income uncertainty. Additionally, the pandemic indirectly influenced savings by affecting household expenditure. These findings highlight the financial vulnerability of lower-income households during economic disruptions and underscore the importance of enhancing financial resilience. Policy recommendations include promoting financial literacy, expanding access to financial resources, and providing targeted support to help households navigate future economic crises.